Research of Pathogenesis and Novel Therapeutics in Arthritis 2.0 - Tang, Chih-Hsin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Arthritis has a high prevalence globally and includes over 100 types, the most common of which are rheumatoid arthritis, osteoarthritis, psoriatic arthritis, and inflammatory arthritis. All types of arthritis share common features of the disease, including monocyte infiltration, inflammation, synovial swelling, pannus formation, stiffness in the joints, and articular cartilage destruction. The exact etiology of arthritis remains unclear, and no cure exists as of yet. Anti-inflammatory drugs (NSAIDs and corticosteroids) are commonly used in the treatment of arthritis. However, these drugs are associated with significant side effects, such as gastric bleeding and an increased risk of heart attack and other cardiovascular problems. It is therefore crucial that we continue to research the pathogenesis of arthritis and seek to discover novel modes of therapy. This reprint summarizes the themes of the 29 articles published in our Special Issue "Research of Pathogenesis and Novel Therapeutics in Arthritis 2.0". This reprint details important novel research discoveries that contribute to our current understanding of arthritis.